Antimicrobial-resistance of Escherichia coli in dogs and cats: A scoping review - Rasaq A. Ojasanya; J. Scott Weese; Zvonimir Poljak; Kurtis E. Sobkowich; Uththami Kukathasan; Theresa M. Bernardo (PLoS ONE, 2025)
Pathogenic Escherichia coli causes a range of clinical manifestations in dogs and cats, and the use of antimicrobials in pets is associated with the risk of antimicrobial resistance (AMR). Pets contribute to the dissemination of AMR both within their species  and to humans. This study conducts a scoping review to assess the existing evidence on the AMR of E. coli in dogs and cats, noting the purpose of antimicrobial susceptibility testing (AST) and determining the knowledge gaps to inform future research. The search utilized specific and generic strings aligned with the research objectives, spanning databases such as MEDLINE®, Web of Science, Biological Science Collection, AGRICOLA, CAB Direct, and Google Scholar, from January 1990 to July 2023. The study selection included only articles published in English and related to primary research. Following deduplication, the initial search identified 1,205 studies. After a detailed full-text review, 108 independent studies were identified. Studies on the AMR of E. coli in companion animals are largely concentrated in North America and Western Europe. Most of the studies were observational and were conducted in veterinary clinics. AST was primarily conducted to guide the antimicrobial treatment of E. coli infections in pets. Although not all studies provided clinical histories, among those that did, multi-drug resistant (MDR) E. coli was reported in both healthy and ailing pets. The detection of MDR E. coli in healthy and sick pets serve as a clarion call for antimicrobial stewardship. However, the limited number of studies dedicated to AMR monitoring and surveillance programs for companion animals raises a substantial concern.